Hubungan Riwayat Gejala Penyakit Infeksi dan Sanitasi Dengan Status Gizi Anak Usia 6-12 Tahun di UPT SDN 060831 Medan - Yusuf Hanafiah (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Deficiency and excess nutrition can affect the growth and development of children. Several factors can affect nutritional status, namely symptoms of a history of infectious diseases and environmental sanitation. To determine the relationship between a history of infectious disease symptoms and environmental sanitation on the nutritional status of children aged 6-12 years. This research is a quantitative research and the research design used is analytic observational with a cross-sectional approach. The population in this study were all students at UPT SDN 060831 aged 6-12 years. The sample used was 225 students selected by statistical random sampling method. Data collection was carried out by measuring the child's weight and height and filling out questionnaires. Statistical test using Spearman test. Statistical test results showed that there was no relationship between a history of infectious disease symptoms and the nutritional status of children aged 6-12 years at UPT SDN 060831 because the ρ value was 0.147 or > 0.05. While the statistical test results also showed that there was a relationship between environmental sanitation and the nutritional status of children aged 6-12 years at UPT SDN 060831 with a ρ value of 0.000 or < 0.05 with a correlation coefficient of 0.313 meaning that the level of relationship strength was sufficient. The nutritional status of children at UPT SDN 060831 in 2023 is not affected by symptoms of infectious diseases (ISPA and Diarrhea) where research on the history of symptoms experienced by children is only in the last 1 month.